Fire extinguisher - Alisa Tong Yen Fang, Alisa Tong Yen Fang; Wong Yan Gi, Wong Yan Gi; Othman, Siti Amira (Penerbit UTHM, 2020)
Fire extinguisher is a safety product that can be found almost everywhere, yet it is the one product that everyone often neglect. In order to understand more about fire extinguishers, we must first know the different classes of fire and then the suitable type of fire extinguishers used. Table 1 summarises the classes of fire and its sources (Fire Extinguisher Types - Fire Protection Equipment & System, March 5, 2019). Table 2, on the other hand, summarises the types of fire extinguishers and the fires suitable to be used for (Surrey Fire & Safety Ltd., April 6, 2018).